Biochemical Characterization of a Spearmint Mutant That Resembles Peppermint in Monoterpene Content - Croteau, Rodney (1991)
A radiation-induced mutant of Scotch spearmint (Mentha × gracilis) was shown to produce an essential oil containing principally C3-oxygenated p-menthane monoterpenes that are typical of peppermint, instead of the C6-oxygenated monoterpene family characteristic of spearmint. In vitro measurement of all of the enzymes responsible for the production of both the C3-oxygenated and C6-oxygenated families of monoterpenes from the common precursor (−)-limonene indicated that a virtually identical complement of enzymes was present in wild type and mutant, with the exception of the microsomal, cytochrome P-450-dependent (−)-limonene hydroxylase; the C6-hydroxylase producing (−)-trans-carveol in the wild type had been replaced by a C3-hydroxylase producing (−)-trans-isopiperitenol in the mutant. Additionally, the mutant, but not the wild type, could carry out the cytochrome P-450-dependent epoxidation of the α,β-unsaturated bond of the ketones formed via C3-hydroxylation. Although present in the wild type, the enzymes of the C3-pathway that convert trans-isopiperitenol to menthol isomers are synthetically inactive because of the absence of the key C3-oxygenated intermediate generated by hydroxylation of limonene. These results, which clarify the origins of the C3- and C6-oxygenation patterns, also allow correction of a number of earlier biogenetic proposals for the formation of monoterpenes in Mentha.